Easter bonnet murder ebook - Meier, Leslie (Lucy Stone,, 2022)
Fans of small-town cozy mysteries will cherish this beloved holiday novella from the collection Gingerbread Cookie Murder is made available for the first time as an e-book single! Known for its cheerful staff and elaborate annual Easter Bonnet Contest, the Heritage House senior center regularly attracts new residents and positive press. But once the town's retired librarian, Miss Julia Tilley, checks in to recover from an illness, Lucy sees a side of the facility that isn't quite so perfect and pristine. And the place may soon be making headlines for different reasons following an unexplained disappearance . . . Lucy can't fathom how Agnes Neal could go missing from assisted living over a silly Easter bonnet contest, or why few seem concerned as signs point to foul play. A retired journalist with an independent mind, Agnes had an eye for details and little interest in conforming to catty cliques or rules set by her caretakers—traits that threatened some and angered others. Gathering clues as flimsy as a half-eaten milk chocolate bunny, Lucy must discover what happened to Agnes—before her own story becomes another springtime tragedy left unsolved.